Understanding the political economy of the Arab uprisings - Diwan, Ishac (World Scientific, 2014)
This book analyzes the political and economic forces that shaped the Arab uprisings of 2010-2011 and the challenges that emerged in their aftermath. It examines the interests, roles, and constraints of key social and political actors involved in democratic transitions and reform efforts. The contributors explore the roots of the uprisings, the dynamics of political change, the role of Arab capitalism, and lessons drawn from countries such as Indonesia, Turkey, and Iran. The volume offers a comparative perspective on the trajectory of the Middle East following the protest movements.